Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2006
DOI: 10.1080/07357900500449603
|View full text |Cite
|
Sign up to set email alerts
|

Lipid Peroxidation and Antioxidant Status in Stomach Cancer

Abstract: We conclude that increased MDA levels and decreased antioxidant enzyme activities can be valuable parameters in assessing the possible risk of cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 23 publications
2
22
0
Order By: Relevance
“…The present study is in agreement with the studies done on gastric cancer antioxidant status by Batcio gluk et al (8), Arivazhagan et al (10), Dincer (21,22) and also studies done on inflam matory bowel disease (23), colorectal cancer (24,25) and bladder cancer (26). Thus, the results of the present study are in accord with those of previous studies.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…The present study is in agreement with the studies done on gastric cancer antioxidant status by Batcio gluk et al (8), Arivazhagan et al (10), Dincer (21,22) and also studies done on inflam matory bowel disease (23), colorectal cancer (24,25) and bladder cancer (26). Thus, the results of the present study are in accord with those of previous studies.…”
Section: Discussionsupporting
confidence: 82%
“…Several recent studies done by Ebubekir et al (7) and Batcioglu et al (8), point out the role of oxidative stress in gastric cancer. It is known that free radicals cause protein damage and degradation (2).…”
Section: Discussionmentioning
confidence: 99%
“…Excess oxidative stress (or primarily its mediators-excess ROS/RNS) within cancer cells has been linked to promotion and progression of malignancy of cancers (Brown & Bicknell, 2001;Klaunig & Kamendulis, 2004;Ray et al, 2000;Tas et al, 2005;Toyokuni et al, 1995). Thus oxidative stress and antioxidant status have been examined in various malignant cancers, such as breast (Brown & Bicknell, 2001;Kang, 2002;Ray et al, 2000;Tas et al, 2005), prostate (Aydin et al, 2006;Sikka, 2003), colorectal (Otamiri & Sjodahl,1989;Oxdemirler et al, 1989), renal (Asal et al, 1990;Gago-Dominguez et al, 2002), and other malignancies (Batcioglu et al, 2006;Manoharan et al, 2005;Seril et al, 2003). In all of these cancers ROS/RNS were in excess of antioxidant concentrations, resulting in cellular oxidative stress.…”
Section: Oxidative Stress and Damage To Mitochondrial Membranes -Relamentioning
confidence: 99%
“…In cancer patients mitochondrial membranes as well as other cellular membranes are especially sensitive to oxidative damage by ROS/RNS, which occurs at high rates in cancer (Batcioglu et al, 2006;Dianzani, 1993;Gago-Dominguez et al, 2002;Manoharan et al, 2005;Otamiri & Sjodahl, 1989;Oxdemirler et al, 1989;Seril et al, 2003). Oxidation of membrane phospholipids alters their structure, affecting lipid fluidity, permeability and membrane function (Dianzani, 1993;Nicolson et al, 1977;Subczynski & Wisniewska, 2000).…”
Section: Molecular Replacement Of Oxidized Membrane Components and Itmentioning
confidence: 99%
“…In previous studies, it has been demonstrated that ROS are directly suggested in oxidative damage of cellular macromolecules such as lipids, proteins, and nucleic acids in tissues (6). Moreover, oxidative stress can lead to tumor angiogenesis.…”
Section: Introductionmentioning
confidence: 99%